(3GdJRGe GdeDLQ HGdVeGf ai GdbGfhfjf GdeUQi hGdGQOfj (B/ s - (3GMeO Ydi Ndja GdYhjOjs; (3eMeO TcQi SQhQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2005)
(3jYJHQ YbO GdGjLGQ ef GdYbhO GdegeI ai MjGI GdGfSGf (B: (3hdG jcGO jhLO GfSGf Ydi hLg GdHSjWI GdG hjONd ai YdGbI GjLGQjI (B: (3hjMJd YbO GdGjLGQ ecGfI eQehbI Hjf ZjQg ef GdYbhO (B: (3deG jeKdg ef GgejI GLJeGYjI hGbJUGOjI hbGfhfjI cHjQI (B: (3HGYJHGQg jbY ai eQcR GdUQGY GdGLJeGYi Hjf eWGdH GdeSJCLQjf GdWGeMjf Gdi GdGeGf hGdebGheI ef LGfH GdedGc (B: (3hgPG eG jLYd egeI GdeTQY ai GdJhajb Hjf GdeUGdM GdeJTGHcI hGdeJVGQHI egeI UYHIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfj, (B2005s
(3HHdjhLQGajG(B: (3UaMGJ (B327345s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3eaghe GdVeGfs; (3GdJRGe GdeDLQ HVeGf GdJYQVs; (3GKGQ GdGdJRGe HGdVeGfs; (3fXQjI GdSHH s; (3fXQjI YOe GdJfajPs; (3GdJRGe GdeDLQ HVeGf GdYjHs; (3OYhi GdVeGfs; (3GdJYQV GdeGOi s; (3GdJYQV GdbGfhfis; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs